Menstrual Blood: A Valuable Source for Regenerative Medicine - Pinnamaneni, Rajasekhar (Indian Journal of Pharmacy Practice)
Menstrual blood is a rich source of stem cells, the endometrium-lining of the uterus regenerates every month. Research on stem cells provides knowledge about how healthy cells replace damaged ones in adults, leading to the possibility of cell-based therapy to treat diseases. Menstrual Stem Cells (MenSCs) show multipotency by directionally differentiating into chondrogenic, adipogenic, osteogenic, neurogenic, and cardiogenic cell lineages. These studies demonstrate the plasticity of MenSCs for potential research in regenerative medicine. Researchers seeking new and more abundant sources of stem cells for use in regenerative medicine have identified a potentially unlimited, noncontroversial, easily collectable, and inexpensive source- menstrual blood.
Keywords: Menstrual Blood; stem cell; MenSCs; Regenerative Medicine